Chloroplast DNA sequence utility for the lowest phylogenetic and phylogeographic inferences in angiosperms: The tortoise and the hare IV1. Issue 11 (1st November 2014) - Shaw, Joey; Shafer, Hayden L.; Leonard, O. Rayne; Kovach, Margaret J.; Schorr, Mark; Morris, Ashley B.
Abstract : Premise of the study: Noncoding chloroplast DNA (NC‐cpDNA) sequences are the staple data source of low‐level phylogeographic and phylogenetic studies of angiosperms. We followed up on previous papers (tortoise and hare II and III) that sought to identify the most consistently variable regions of NC‐cpDNA. We used an exhaustive literature review and newly available whole plastome data to assess applicability of previous conclusions at low taxonomic levels. Methods: We aligned complete plastomes of 25 species pairs from across angiosperms, comparing the number of genetic differences found in 107 NC‐cpDNA regions and matK . We surveyed Web of Science for the plant phylogeographic literature between 2007 and 2013 to assess how NC‐cpDNA has been used at the intraspecific level. Key results: Several regions are consistently the most variable across angiosperm lineages: ndhF‐rpl32, rpl32‐trnL (UAG), ndhC‐trnV (UAC), 5′rps16‐trnQ (UUG), psbE‐petL, trnT (GGU) ‐psbD, petA‐psbJ, and rpl16 intron. However, there is no universally best region. The average number of regions applied to low‐level studies is ∼2.5, which may be too little to access the full discriminating power of this genome. Conclusions: Plastome sequences have been used successfully at lower and lower taxonomic levels. Our findings corroborate earlier works, suggesting that there are regions that are most likely to be the most variable. However, while NC‐cpDNA sequences are commonly used in plant phylogeographic studies, few of the most variable regions are applied in that context. Furthermore, it appears that in most studies too few NC‐cpDNAs are used to access the discriminating power of the cpDNA genome.